Agronomic and economic implications of cover crop and phosphorus fertilizer management practices for water quality improvement. Issue 1 (9th December 2022) - Nelson, Nathan O.; Roozeboom, Kraig L.; Yeager, Elizabeth A.; Williams, Jeffery R.; Zerger, Sarah E.; Kluitenberg, Gerard J.; Tomlinson, Peter J.; Abel, David S.; Carver, R. Elliott
Abstract: Phosphorus (P) fertilization practices and winter cover crops are promoted to protect water quality yet can potentially influence crop yield and profitability. This study examined the impacts of three P fertilizer management practices (no P, fall broadcast P, and spring injected P) and winter annual cover crop use on yields, net returns, and water quality in a no‐till corn–soybean rotation. Treatments were replicated in a 4‐yr field study where sediment, total P, and dissolved reactive P (DRP) losses in edge‐of‐field surface runoff were continuously monitored. Production budgets were developed for each treatment and coupled with water quality data to identify optimal practices and opportunity costs for improving water quality. Applying P fertilizers increased crop yield regardless of application method or cover crop, but the response was more pronounced in corn than soybean. The cover crop reduced corn grain yield in 1 yr with high temperature and low precipitation but did not impact grain yield in the other corn year or either year of soybean. The most profitable treatment was fall broadcast P fertilizer with no cover crop, which also had the greatest total P and DRP losses and near greatest sediment loss. The lowest‐cost methods of reducing total P, DRP, and sediment losses were, respectively, no P fertilizer without a cover crop ($47.56 kg −1 total P), spring injected P fertilizer without a cover crop ($56.47 kg −1 DRP), and spring injected P fertilizer with a cover crop ($0.16 kg −1 sediment). Widespread adoption of these practices will likely require monetary incentives. Core Ideas: The most profitable system was fall broadcast P fertilizer with no cover crop, which also had the greatest P loss. Spring injected P fertilizer reduced dissolved reactive P loss in surface runoff at a cost of $56.47 kg −1 of dissolved reactive P. Cover crops reduced sediment loss in surface runoff at a cost of $0.16 kg −1 of sediment. Producers will likely need incentives to adopt cover crops or spring injected P fertilizer management.